Economic Impact of THE PLAYERS Championship Golf Tournament at Ponte Vedra Beach, Florida, March 2005 - Tom Stevens; Alan Hodges; David Mulkey (EDIS)
FE698, a 3-page paper by Tom Stevens, Alan Hodges, and David Mulkey reports estimates of economic impacts in order to assess the importance of TPC golf tournament to the northeast Florida economy and to the industries and institutions within it. Published by the UF Department of Food and Resource Economics, October 2007.